Prolactin is associated with bone mineral density in subjects with type 2 diabetes mellitus - Chen, Jia; Liu, Geng; Li, Quan; Deng, Wei (Frontiers in Endocrinology, 2022)
Purpose Prolactin (PRL) exerts actions in the bone besides lactation and reproduction. This study aimed to investigate whether PRL is related to bone mineral density (BMD) in type 2 diabetes mellitus (T2DM). Methods A total of 642 patients with T2DM were divided into two groups with age and body mass index (BMI) matched: mildly increased PRL (HP group, n = 101) or normal PRL (NP group, n = 541). BMD was measured by dual-energy X-ray absorptiometry and compared. Results 1) BMD, T score at lumbar spine L1–4, right hip and femur neck, and Z score at the femur neck were significantly higher in the HP than in the NP group (0.96 ± 0.16 vs. 0.92 ± 0.15g/cm2, p = 0.019; 0.88 ± 0.15vs. 0.84 ± 0.14 g/cm2, p = 0.007; 0.75 ± 0.17 vs.0.70 ± 0.13 g/cm2, p = 0.001; -0.90 (-1.85, -0.20) vs. -1.40 (-2.20, -0.40), p = 0.018; -0.80 (-1.50, -0.30) vs. -1.10 (-1.80, -0.53), p = 0.026; -1.30 (-2.00, -0.60) vs. -1.70 (-2.20, -1.00), p = 0.001; -0.20 (-0.70, 0.30) vs. -0.40 (-0.90, 0.10), p = 0.026). In men, T and Z scores at the right hip and femur neck were significantly higher in the HP than in the NP group (-0.70 (-1.32, 0.20) vs. -0.90 (-1.50, -0.40), p = 0.038; -0.20 (-0.80, 0.20) vs. -0.50 (-0.10, 0.10), p = 0.027; -0.30 (-0.60, -0.30) vs. -0.40 (-0.90, 0.20), p = 0.038) but not in women. Bone turnover markers have no significant difference between groups (all p > 0.05). 2) BMD at the right hip and Z score at the right hip and femur neck were significantly positively associated with PRL (r = 0.087, p = 0.029; r = 0.089, p = 0.024; r = 0.087, p = 0.029). In men, BMD at L1–4 and the right hip; T score at L1–4, the right hip, and the femur neck; and Z score at the right hip and the femur neck were significantly positively associated with PRL (r = 0.122, p = 0.007; r = 0.105, p = 0.041; r = 0.123, p = 0.016; r = 0.110, p = 0.032; r = 0.115, p = 0.025; r = 0.121, p = 0.018; r = 0.138, p = 0.007) but not significant in women. 3) In men divided into two groups according to T score (T score at the right hip>-1 or T score at the right hip≤-1) or the median BMD at L1–4, the right hip or the femur neck, PRL was significantly higher in the higher BMD than in the lower BMD group (16.32 ± 6.12 vs. 14.78 ± 5.68 ng/ml, p = 0.012; 16.20 ± 6.21 vs. 14.73 ± 5.40 ng/ml, p = 0.014; 16.10 ± 6.01 vs. 14.80 ± 5.77 ng/ml, p = 0.032; 16.17 ± 6.04 vs. 14.76 ± 5.77 ng/ml, p = 0.02; 16.48 ± 6.05 vs. 14.98 ± 5.81 ng/ml, p = 0.020; 16.10 ± 5.98 vs. 14.80 ± 5.87 ng/ml, p = 0.035). Conclusion Increased PRL was associated with better BMD in patients with T2DM, especially in men. PRL within the biologically normal range may play a protective role in the BMD of T2DM.